Asymmetric and symmetric dimethylarginine as markers of endothelial dysfunction in cerebrovascular disease: A prospective study - Bima, Chiara; Parasiliti-Caprino, Mirko; Rumbolo, Francesca; Ponzetto, Federico; Gesmundo, Iacopo; Nonnato, Antonello; Fornengo, Paolo; Vaula, Giovanna; Ghigo, Ezio; Mengozzi, Giulio; Settanni, Fabio (Nutrition, metabolism, and cardiovascular diseases, 2024)
Asymmetric dimethylarginine (ADMA) and symmetric dimethylarginine (SDMA) have been proposed as mediators of endothelial dysfunction. In this study, we aimed to investigate the diagnostic and prognostic role of ADMA and SDMA in acute cerebrovascular disease. A prospective case-control study was performed, enrolling 48 patients affected by ischemic stroke with no cardioembolic origin, 20 patients affected by TIA, 40 subjects at high cardiovascular risk and 68 healthy subjects. ADMA levels were significantly lower in high-risk subjects (18.85 [11.78–22.83] μmol/L) than in patients with brain ischemic event, both transient (25.70 [13.15–40.20] μmol/L; p = 0.032) and permanent (24.50 [18.0–41.33] μmol/L; p = 0.001). SDMA levels were different not only between high-risk subjects and ischemic patients, but also between TIA and stroke patients, reaching higher levels in TIA group and lower levels in stroke group (1.15 [0.90–2.0] vs 0.68 [0.30–1.07] μmol/L; p < 0.001). SDMA was also correlated with short-term prognosis, with lower levels in case of adverse clinical course, evaluated by type of discharge (p = 0.009) and need of prolonged rehabilitation (p = 0.042). The present study highlights the relationship between l-arginine, ADMA, SDMA and acute cerebrovascular events. Therefore, our results suggested a potential role of SDMA as a specific marker of transient ischemic damage and as a short-term positive prognostic marker. •ADMA, SDMA and their ratio with l-arginine are markers of endothelial dysfunction.•SDMA seems to be specific for the diagnosis of transient ischemic damage.•SDMA are inversely proportional to oxidative stress degree and may be a laboratory indicator of the extent of the neurological deficit and as a short-term positive prognostic marker in the patients affected from ischemic stroke.•ADMA, SDMA and their ratio with l-arginine may represent a new diagnostic and prognostic tool in the management of cardio-cerebrovascular diseases.